Association of Hypertensive Disorders of Pregnancy with variations in Serum Sodium and Potassium Concentration - Umairah yaqub; Irfan Khattak; Samina Naseem; Ayesha Imran; Khawar Kamal; Abbas Niazi (Pakistan Armed Forces Medical Journal, 2023)
Objective: To study the variation in Serum Sodium and Potassium concentration in Pre-eclampsia and Normotensive pregnant ladies.